Prophets with Lying Spirit? Nigerian Prophets, Prophecies, and an Endangered Democracy - Agara, Tunde; Adetunji, Emmanuel (African Journal of Stability and Development (AJSD), 2022)
This paper is a theoretical empirical study derived from what has become a recurring decimal each time Nigeria is preparing for general elections. Our experience over the years has shown that electioneering processes in Nigeria comes with different prophesies about the eventual outcomes of the elections by prophets claiming to know the mind of God or having exclusive insights on the candidates whom God has chosen. Most of these prophecies are contradictory to some others, sometimes, implying that there are different gods responsible for revealing the prophecies to the prophets. These prophecies embolden the different aspirants that they are the chosen ones and hence boosts their expectations of victory at the polls, sometimes without carrying out the usual electioneering process of campaigning, having manifestoes and trying to win the electorates legitimately. Of further concern to us is that the belief in the prophecies trickle down to the electorates by influencing their choices. When their candidate eventually fails to win, then the elections are seen to have been tampered with and declared unfair. Most often, this leads to rioting, violence and attendant vandalisation of properties and loss of lives. The candidate who fails to win election goes to court and a process of unnecessary prolonged litigation ensues. Thus, virtually every elections end in contestation in court thereby making a mockery of election and the electioneering process. This tendency is what this paper interrogates, especially as it touches on endangering democracy in Nigeria.